EKSPEKTASI DAN PERSEPSI WISATAWAN TERHADAP KUALITAS PELAYANAN PADA MARINA SRIKANDI TOUR & TRAVEL DI PADANGBAI - Natha Dwipayana, Made; Suwena, I Ketut; Indrawati, Yayu (Jurnal IPTA (Industri Perjalanan Wisata), 2013)
Differences between expectation and perception of visitor about service quality of a travel agency were the background of this research which is entitled “Visitor’s Perception And Expectation of Service Quality At Marina Srikandi Tour And Travel In Padang Bai. Through this research, a thought to maintain professionalism of travel agency with qualified standards, understand different visitor expectations was a major thing that want to be achieved. Background of problem in this research was divided into two problems, such as (1) what are visitor expectation and perception about service quality at Marina Srikandi Tour and travel? (2) How is the visitor’s satisfaction about service quality which is given by Marina Srikandi Tour and travel? Based on the background of problems above, there were two aims of study in this research, they are: (1) to know visitor expectation and perception about service quality at Marina Srikandi Tour and travel, and (2) to know visitor’s satisfaction about service quality which is given by Marina Srikandi Tour and travel.
Keywords: Expectation, Perception, and Service of Quality